PENGARUH PENAMBAHAN TEPUNG HATI AYAM DAN TEPUNG KELOR TERHADAP FISIKOMIAWI COOKIES KAMBAMBANG: The Effect Of Addition Of Chicken Liver Flour And Moringa Flour On The Physicochemical Properties Of Kambambang Cookies - Agnes Rambu Riti; Yessy Tamu Ina (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2026)
Kambambang is a traditional food of the Sumbanese people that contains cultural values of local wisdom and needs to be preserved. However, its processing is still limited because it generally uses only cassava flour, grated coconut, and sugar, resulting in relatively low nutritional value and limited potential for development as a modern snack. Therefore, this study aimed to analyze the effect of adding moringa leaf flour and chicken liver flour on the physicochemical characteristics of kambambang cookies. This study used four treatments: P1 (3%), P2 (5%), P3 (7%), and P4 (9%). The parameters analyzed included water content, pH, organoleptic properties (color, taste, texture, and preference level), and iron (Fe) content measured using the ICP-OES method. The results showed that increasing the level of fortification affected several characteristics of the cookies. Treatment P4 (9%) produced the lowest water content with a pH value within the normal range, slightly brown color, and a slightly crunchy texture, while panelist acceptance was categorized as somewhat preferred. Meanwhile, treatment P2 (5%) showed the highest level of preference and optimal iron content compared to other treatments. Consumption of 100 g of cookies from the best treatment was able to contribute approximately 15–16% of the daily iron requirement for adolescent girls. Overall, fortification with moringa leaf flour and chicken liver flour has potential to improve nutritional value, especially iron content, while maintaining acceptable sensory quality.